Analisa Optimasi Diameter Jaringan Pipa Distribusi Air Bersih Dengan Menggunakan Software EPANET, LINGO di Jalur Sentul City PDAM Tirta Kahuripan Kabupaten Bogor - Nuryani Nuryani; Budi Santosa (Rekayasa Sipil, 2020)
One of the most important roles of water system supply is piping networking. Performance of water supply sistem service is determined not only by a capacity from the source, but also by water volume which must also be up to the vertices with high flow and adequate pressure as needed. Besides, the effectiveness of a pipline is measured from the cost of investment and operational cost over life of specified order. In order to achieve adequate pressure and flow conditions it must be analyzed the size carefully. Linear programming represents the completion of operations research techniques that can solve optimization problems. Linear prograsmming is used to minimize cost size of pipe. On this research, a sample informartion taken by a clean water distributin network in PDAM Tirta Khuripan, Bogor, West Java. By using the method of linear programing the result of optimization in PDAM Tirta Khuripan, Bogor, West Java diameter on each pipe  in with the selection of the main pipe diameter between 8 inch to 22 inch and pressure energy or relative energy is 2 metes into 7 metes by license set.